ATIVIDADE CELULOLÍTICA DE FUNGOS AEROBIOS ISOLADOS DO RÚMEN DE BOVINOS LEITEIROS ALIMENTADOS COM FORRAGENS TROPICAIS - PATRÍCA NATALÍCIA MENDES ALMEIDA; CLÁUDIO EDUARDO SILVA FREITAS; FLÁVIA OLIVEIRA ABRÃO; IZABELLA CAROLINA OLIVEIRA RIBEIRO; EDVALDO ALVES VIEIRA; LUCIANA CASTRO GERASEEV; EDUARDO ROBSON DUARTE (Revista Caatinga, 2014)
The objective was to evaluate the cellulolytic activity of aerobic mycelian fungi from dairy cat- tle fed tropical forages. Isolates of fungi were obtained from 30 samples of rumen fluid from cows fed sorghum silage, 32 cows fed on Brachiaria brizantha , 12 heifers receiving sorghum silage and 11 heifers fed cane sugar. The isolation was performed on C solid medium containing cellulose. Were evaluated 49 isolates, 27 Aspergil- lus spp., four Gliocladium spp., six Paecilomyces spp., nine Rhizophus spp. and three Scedosporium . These isolates were incubated in C medium with 1% microcrystalline cellulose as the sole carborno source, and incu- bated at 37°C in triplicate. Cellulolytic activity indices were verified after 24, 48 and 72 hours and calculated by the ratio between degradation halo and colony diameter for comparing in nonparametric tests. The genus Aspergillus , showed higher cellulolytic activity index mean compared to Rhizophus genus (p <0.05). Eight iso- lates of Aspergillus spp. and six of Paecilomyces spp. showed this index higher than one, indicating potential for utilization in ruminant nutrition.